2011
DOI: 10.1002/maco.201005857
|View full text |Cite
|
Sign up to set email alerts
|

Metallic interconnects for solid oxide fuel cell: Performance of reactive element oxide coating during long time exposure

Abstract: One of challenges in improving the performance and cost-effectiveness of SOFCs (solid oxide fuel cells) is the development of suitable interconnects materials. Chromia-forming alloys and especially ferritic stainless steels, like Crofer22APU, are considered to be among the most promising candidate materials as interconnects in SOFC stacks. However, the performance of chromia-forming materials can be limited by the low electronic conductivity of the oxide scale (high ASR -area specific resistance -value). Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The oxide scale of Crofer 22 APU is composed of a chromia inner layer and a (Mn,Cr) 3 O 4 spinel outer layer, which is formed by the diffusion of Mn along the grain boundaries of the chromia scale. 88 The boundary between the Mn-Co spinel protection layer and the Mn-Cr spinel intrinsic scale on Crofer 22 APU is not clearly observed, which suggests that the coating layer and the substrate are chemically and thermo-mechanically compatible, forming the strong interface. Figure 6 compares the ASR data of the bare and coated Crofer 22 APU samples measured at 800…”
Section: Resultsmentioning
confidence: 98%
“…The oxide scale of Crofer 22 APU is composed of a chromia inner layer and a (Mn,Cr) 3 O 4 spinel outer layer, which is formed by the diffusion of Mn along the grain boundaries of the chromia scale. 88 The boundary between the Mn-Co spinel protection layer and the Mn-Cr spinel intrinsic scale on Crofer 22 APU is not clearly observed, which suggests that the coating layer and the substrate are chemically and thermo-mechanically compatible, forming the strong interface. Figure 6 compares the ASR data of the bare and coated Crofer 22 APU samples measured at 800…”
Section: Resultsmentioning
confidence: 98%
“…Several materials have been investigated as protective coatings for SOFC interconnects, including rare-earth oxides [15,16] and various lanthanum-based perovskites [17][18][19]. (Mn,Co)3O4 spinel oxides were first suggested as a coating material candidate by Larring and Norby [20], and have received increasing attention over the last decade [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive element oxides could be coated to provide the reactive element effect including the reduced oxidation rate of the alloys. Fontana et al [100] demonstrated that the addition of a nanometric reactive element oxide (La2O3, Y2O3) layer applied by Metal Organic Chemical Vapour Deposition (MOCVD) drastically improved both corrosion rate and electrical properties in air of Crofer 22 APU and Haynes 230 alloys even after 20 months exposure at 800 ºC in air. During aging in SOFC conditions, La2O3 transformed into LaCrO3.…”
Section: Influence Of Coatingsmentioning
confidence: 99%